2019
DOI: 10.1371/journal.pone.0218380
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of an HIV education program for primary care providers: Screening and late diagnosis rates

Abstract: Background Late HIV diagnosis remains one of the challenges in combating the epidemic. Primary care providers play an important role in screening for HIV infection. Our study aims to evaluate the relationship between knowledge and barriers to HIV testing and screening outcomes. The impact of an education program for primary care providers, towards improving HIV testing and late diagnosis rates, is also assessed. Methods A self-administered questionnaire that was develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Previous studies in the same health area found rates of new HIV diagnoses higher than 2‰, 22,23 while five years later the incidence was 0.44‰. Although no definitive conclusions can be drawn, these data may indicate that the low prevalence of chronic occult infection currently existing in our area may be due to the effectiveness of screening programmes implemented in recent years, 18,23 as well as to the progressive decrease in the global incidence of HIV infection 24 . Moreover, patient characteristics included in the study could explain in part this low number of HIV diagnoses, since there is a high representation of women and people over 50 years of age.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies in the same health area found rates of new HIV diagnoses higher than 2‰, 22,23 while five years later the incidence was 0.44‰. Although no definitive conclusions can be drawn, these data may indicate that the low prevalence of chronic occult infection currently existing in our area may be due to the effectiveness of screening programmes implemented in recent years, 18,23 as well as to the progressive decrease in the global incidence of HIV infection 24 . Moreover, patient characteristics included in the study could explain in part this low number of HIV diagnoses, since there is a high representation of women and people over 50 years of age.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, an evaluation of ICguided HIV testing recommendations in specialty guidelines in the UK and Europe revealed that the majority of IC guidelines do not recommend HIV testing, and physicians are not always aware of current HIV testing recommendations. [18,37] This is supported by the observation that the highest HIV test ratio were found in TB, HBV and HCV; HIV testing is recommended most prominently in the specialty guidelines for these conditions, and as pulmonologists and gastroenterologists commonly collaborate with infectious disease specialists, they may be more likely to focus on possible underlying HIV. Adoption of HIV testing in specialty guidelines and creating awareness of this strategy among involved specialties is an important first step to optimize testing.…”
Section: Discussionmentioning
confidence: 95%
“…Universal opt-out HIV testing programs offered to all general medical admissions in a hospital have proven effective in improving HIV diagnosis in several studies ( 19 ). Formative strategies have proven to be helpful in primary care ( 17 , 18 , 20 ). However, data on these strategies in hospital settings are scarce.…”
Section: Discussionmentioning
confidence: 99%